SIRTLAR OILASINING O‘RAMASI (Multidisciplinary Journal of Science and Technology, 2026)
In recent years, the science of differential geometry has developed, and interest in its practical and theoretical directions is growing. In particular, the study of surfaces and their properties, including the study of the geometry of surface wrappings, has become one of the most relevant issues due to its direct connection with such disciplines as physics, engineering, and computer graphics. Surface wrappings are an important tool for describing the shape and state of surfaces, their representation and analysis in space. This area is widely used not only theoretically, but also in practice. This further increases the scientific and practical significance of the topic. The main purpose of this article is to deeply study the concept of surface wrappings, analyze their differential-geometric properties, and derive formulas for curvature, normal vectors, and other important elements for certain types of surface wrappings. The object of research is smooth surfaces in space and differential-geometric objects related to their wrappings.The article studies the differential-geometric properties of some special types of surface wrappings. Their main and secondary forms, curvature components, and their interrelationships are determined. Also, an analysis of surface wrappings based on specific examples is given and new results are presented.